If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-63-13x=-5x+121
We simplify the equation to the form, which is simple to understand
-63-13x=-5x+121
We move all terms containing x to the left and all other terms to the right.
-13x+5x=+121+63
We simplify left and right side of the equation.
-8x=+184
We divide both sides of the equation by -8 to get x.
x=-23
| 42x-18x^2=0 | | -7.5x+3=-27 | | 3x-4+2x=-3x+28 | | 2-x/4=1-x/6 | | 5=18-x/3 | | -7(s-2)=12 | | 3y-5y=-16 | | -201-4x=11x+54 | | -22-8x=12-9x | | -3(3-x)=2x+5 | | r-2(14)=14 | | -21-11x=-13x+29 | | 5n-7=3n+5 | | 2x/5+1=3 | | P=2b+2c | | x-81=-9x+99 | | -15(y+2)=-20 | | 195=r*3 | | x3/3+4x2+22x=0 | | 8x-4-5x=x+7+x | | x3/3+4x2+22x | | 8x-4-5x=x+7+7 | | 24=0 | | 15x+1=24 | | 7x+6=10x+2 | | 10+8x=24 | | 9+6x+2x-1=24 | | xa-H=2ab+C | | 42x-2x^2=0 | | -4+3x=4x-8 | | 3a(6a-5)+4=10 | | 6=w+37 |